A cation selective separator induced cathode protective layer and regulated zinc deposition for zinc ion batteries. Issue 8 (28th January 2021) - Wu, Buke; Wu, Yize; Lu, Zhendong; Zhang, Jianshuo; Han, Ning; Wang, Yameng; Li, Xiao-min; Lin, Meng; Zeng, Lin
Abstract : The present work investigates the application of a Nafion separator in aqueous zinc ion batteries. Abstract : The widespread application of aqueous rechargeable zinc ion batteries (ARZIBs) is limited by issues from both electrodes, including poor reversibility of the zinc anode and low capacity of the cathode. Here, we report the application of a Zn 2+ substituted Nafion separator (Zn-Nafion) in ARZIBs which improves the performance of both the cathode and anode. On the anode side, the Zn-Nafion separator creates a uniform electrical and Zn 2+ concentration field near the zinc anode surface, resulting in limited zinc dendrite growth. Therefore, a Zn symmetric cell with a Zn-Nafion separator shows a lower polarization and longer cycle life than those applying a traditional glass fiber separator. On the cathode side, the Zn-Nafion separator increases the contribution of the H + reaction in the H + /Zn 2+ co-insertion process, and causes the randomly distributed byproducts, Zn4 SO4 (OH)6 · n H2 O platelets, to transform into a dense solid-electrolyte-interphase layer, which protects the cathode from dissolving into the electrolyte. Thus, the energy density and capacity retention of both zinc full cells (applying commercial V2 O5 or α-MnO2 nanowires as the cathode) are dramatically improved by the Zn-Nafion separator. Notably, the Zn//Zn-Nafion//V2 O5 cell delivers a high specific capacity of 495.8 mA h g −1 (374.4 W h kg −1 ) with a low cathode cost (39.23 US$ W h kg −1 ). Moreover, the Zn-Nafion separator can be recycled at least ten times without performance degradation, which significantly reduces the cost of the battery. The present work can provide a novel insight into cost-effective and high-performance battery technologies.